PERBANDINGAN KOMPRES HANGAT DAN KOMPRES DINGIN TERHADAP PENURUNAN SUHU TUBUH ANAK DEMAM USIA 1-5 TAHUN - janiah, Janiah; Nining Sriningsih; RinaPuspita Sari (Pusat Riset dan Inovasi Nasional, 2022)
Fever is described as an increase in body temperature due to an increase in the hot area in the hypothalamus. Fever can be dangerous if the temperature rises quickly. This study aims to compare the temperature of children with fever using warm compresses and cold compresses. This study uses a quasi-experimental method of Non-Randomized Two Group Pre-Test-Post-Test. This research was conducted at the Tangerang Regency General Hospital with the technique of warm compresses and cold compresses according to the applicable SOP. The actions taken in this study were by giving warm compresses and cold compresses for 15-30 minutes and checking the temperature before and after for 10-15 minutes. The results of this study obtained a comparison between warm compresses and cold compresses on a decrease in body temperature, after a warm compress the effect of a decrease in temperature was 1.43 degrees Celsius, while cold compresses had a decreasing effect of 1.98 degrees Celsius.